2009
DOI: 10.1111/j.1525-1470.2009.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar Pyoderma Gangrenosum in a Child

Abstract: We present a case of a 10-year-old girl with a diagnosis of vulvar pyoderma gangrenosum. Intravenous methylprednisolone was started and on tapering the steroid regimen, the lesion showed significant enlargement and purulent discharge without any remission of fever and inflammatory activity, so she was treated with oral cyclosporin A in combination with low-dose steroid. A response to treatment was achieved after 2 weeks and clinical and laboratory follow-up at 12 months did not show any disease relapse or infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…Several studies have demonstrated decreased secretion of ADH and a reduced response to antidiuretic hormone in children affected. Moreover, NE may be present with several comorbidities such as sleep disorders, psychological problems, parasomnias, left-handedness, polythelia, language disorders and testicular pathology (8)(9)(10). Various formulations of dDAVP are available (tablets, nasal spray) and many studies also showed that the dosage for MELT is more predictable due to the significantly smaller variance, however there is only limited information on the response to dDAVP in children relative to the dose required to produce an antidiuretic effect for the entire night.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated decreased secretion of ADH and a reduced response to antidiuretic hormone in children affected. Moreover, NE may be present with several comorbidities such as sleep disorders, psychological problems, parasomnias, left-handedness, polythelia, language disorders and testicular pathology (8)(9)(10). Various formulations of dDAVP are available (tablets, nasal spray) and many studies also showed that the dosage for MELT is more predictable due to the significantly smaller variance, however there is only limited information on the response to dDAVP in children relative to the dose required to produce an antidiuretic effect for the entire night.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate and intensive care for these children and their family is essential. (23)(24)(25)(26)(27)(28)(29) Black and colleagues, as a result of their experience with these troubled children, suggested some recommendations that include: immediately after the killing, children's placement should be with familiar people; primary health care services should be alerted about the children and early consultations sought from child mental health services; expert advice should be sought regarding the possibility of attending their mother's funeral and of visiting their father. (9) In the longer term, permanent placement planning should begin as soon as possible: the emergency placement should not become permanent by default; therapeutic help should be available as needed, especially for children who witnessed the killing.…”
Section: Resultsmentioning
confidence: 99%
“…Hier passieren die meisten Anpralltraumen. Auch Unterarme, Schulter, Genitale und Brustbereich sind mögliche Lokalisationen [10,17].…”
Section: Chirurgische Therapie Beim Pyoderma Gangraenosumunclassified